Hadith Analysis of Al-Jallalah: A Crucial Framework for Risk Management in Halal Animal Feed Studies - Saidin, Nurulaina; Yaakob, Mohd Ashrof Zaki; Rahman, Fadilah Abd; Ruzulan, Zulaipa; Samori, Zakiah; Harun, Hanifah Musa Fathullah (Journal of Ecohumanism, 2024)
Hadith are the Prophetic texts that serve as the main reference and guidance for Muslims in their daily life. In the discussion related to the al-Jallalah, two hadiths are commonly identified as references. Nevertheless, based on textual analysis, there are many other hadiths in al-Kutub al-Sittah (The Authentic Six) on the prohibition of al-Jallalah and its meat and milk. This paper aims to identify and analyse all hadith related to the al-Jallalah from al-Kutub al-Sittah using the qualitative method. The discussion focuses on the analysis of the textual Hadith of al-Jallalah that derived from al-Kutub al-Sittah. The study reveals that there are thirteen hadith (13) on the topic of al-Jallalah which specifically related to the prohibition against eating meat, drinking milk, and riding the al-Jallalah animals which derived from Sunan Abi Dawud (9 texts of Hadith), Jami’ al-Tirmidhi (2 texts of Hadith), Sunan al-Nasa’i (1 text of Hadith and Sunan Ibn Majah (1 text of Hadith). In terms of the authenticity of the Prophetic texts pertaining to the al-Jallalah, it is found that out of 13 texts of Hadith, there are eight (8) texts of Hadith Sahih, two (2) texts of Hadith Hasan Sahih, two (2) texts of Hadith Hasan, and only one (1) texts of Hadith Da‘if. It is expected that the findings of this paper could provide useful knowledge and reference related to the prohibition of animals that are categorized as al-Jallalah in al-Kutub al-Sittah (The Authentic Six). Hence, this study establishes a crucial foundation linking hadith analysis of al-Jallalah with risk management in Halal animal feed studies, offering valuable insights and references on this significant Islamic dietary issue.